The Rights of Sasak Noble Muslim Women in Choosing A Mate: an Analysis of The Marriage of Noble Women With Jajar Karang Men From The Perspective of Islamic Law - Azhari, Doni; Qalyubi, Syihabuddin (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article explores several aspects of equality in Banjar Customary marriage law, especially regarding the rights of Sasak noble women in choosing a life partner. The aim is to find out and analyze the rights of Sasak noble women from the perspective of gender and Islamic Law. According to Banjar Customary Law, a noblewoman (menak) cannot marry a jajar karang man (ordinary people). If this is done, the act is considered a nyerompang (violation) which has an impact on the severance of kinship ties and inheritance rights. This study uses the contestation method from Michel Foucault which is applied to study the position and status of men and women in Sasak Society. This study found the fact that two kinds of tendencies are currently developing in Sasak society. First, the group that maintains Customary Law, and second, the group that welcomes change. The emergence of this second group is influenced by several factors, including the influence of local Ulama who offer egalitarianism in Islamic Law to solve marriage problems that arise in society. This study also concludes that there is a relationship between customs strengthened by scholars with the theory of contestation, where customs are normative forces that are maintained and influence the dynamics of power in the context of marriage. The presence of laws, thus, that combine cultural traditions and religious beliefs is needed to achieve gender equality in marriage